Physiological response during germination of Espeletia grandiflora seeds subjected to mechanical blowing processes using forced air (Research, Society and Development, 2023)
When introducing the study of seeds as propagation material of the species, it is necessary to understand the physiological quality attributes as important components that allow further characterisation of the germplasm evaluated. In this sense, the objective of this research was to establish the physiological response during germination of Espeletia grandiflora seeds, subjected to mechanical blowing processes using forced air. The percentage ratio of full and empty seeds, germination percentage, viability and survival, seedling growth given by the length of the stem and number of leaves (nomophylls) formed, as well as the dynamics of germination, growth and survival over time were evaluated, taking as a differentiating factor the mechanical blowing of seeds by forced air (the opening was regulated in arbitrary units). The results showed, for all the variables studied, a marked positive relationship between forced mechanical blowing and the quality of the seeds obtained. In this sense, the seeds with the best values and which differed from the rest of the treatments were those that were subjected to Treatment 4 (heavy seed obtained with an opening of 25 of the vernier gate). Likewise, the least favourable results were obtained for the batch of heavy seeds obtained with an opening of 15 and a slight opening of 20 of the vernier gate (Treatment 2), differing significantly from the rest of the treatments.